Comparison of analgesic efficacy of four‐quadrant transversus abdominis plane (TAP) block and continuous posterior TAP analgesia with epidural analgesia in patients undergoing laparoscopic colorectal surgery: an open‐label, randomised, non‐inferiority trial. (April 2014) - Niraj, G.; Kelkar, A.; Hart, E.; Horst, C.; Malik, D.; Yeow, C.; Singh, B.; Chaudhri, S.
Summary Posterior transversus abdominis plane blocks have been reported to be an effective method of providing analgesia after lower abdominal surgery. We compared the efficacy of a novel technique of providing continuous transversus abdominis plane analgesia with epidural analgesia in patients on an enhanced recovery programme following laparoscopic colorectal surgery. A non‐inferiority comparison was used. Adult patients undergoing elective laparoscopic colorectal surgery were randomly assigned to receive continuous transversus abdominis plane analgesia (n = 35) vs epidural analgesia (n = 35), in addition to a postoperative analgesic regimen comprising regular paracetamol, regular diclofenac and tramadol as required. Sixty‐one patients completed the study. The transversus group received four‐quadrant transversus abdominis plane blocks and bilateral posterior transversus abdominis plane catheters that were infused with levobupivacaine 0.25% for 48 h. The epidural group received an infusion of bupivacaine and fentanyl. The primary outcome measure was visual analogue scale pain score on coughing at 24 h after surgery. We found no significant difference in median (IQR [range]) visual analogue scores during coughing at 24 h between the transversus group 2.5 (1.0–3.0 [0–5.5]) and the epidural group 2.5 (1.0–5.0 [0–6.0]). The one‐sided 97.5% CI was a 0.0 (∞–1.0) difference in means, establishing non‐inferiority. There were no significant differences between the groups for tramadol consumption. Success rate was 28/30 (93%) in the transversus group vs 27/31 (87%) in the epidural group. Continuous transversus abdominis plane infusion was non‐inferior to epidural infusion in providing analgesia after laparoscopic colorectal surgery.